Possible: Transformational change in collective impact*. Issue 2 (14th March 2016) - Weaver, Liz
Abstract: Collective impact (CI) is a framework for community change efforts designed to focus on shifting systems, policy, and environments. The CI framework brings together diverse stakeholders who agree to work together on a complex social or environmental problem. The framework requires engaging different sectors of the community, focusing on the root causes of the problem, and measuring progress over time. Communities implementing CI approaches are witnessing needle-moving shifts in systems, policies, and environments. This paper examines the current state of CI, as well as six essential elements to build toward transformative change, and begins to explore the future of CI.